2011
DOI: 10.1007/s12529-011-9173-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Engagement at Work: Validation of the Chinese Version of the Utrecht Work Engagement Scale

Abstract: BackgroundWork engagement is a positive work-related state of fulfillment characterized by vigor, dedication, and absorption. Previous studies have operationalized the construct through development of the Utrecht Work Engagement Scale. Apart from the original three-factor 17-item version of the instrument (UWES-17), there exists a nine-item shortened revised version (UWES-9).PurposeThe current study explored the psychometric properties of the Chinese version of the Utrecht Work Engagement Scale in terms of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(149 citation statements)
references
References 23 publications
14
121
2
12
Order By: Relevance
“…This result is also consistent with a previous study 12) . In that study, educators, managers and police officers showed high levels of engagement, which was in contrast with a study conducted in China 10) in which support staff were more engaged compared with professional staff. At this moment, we do not have interventional evidence suggesting that educational methods or lifestyle habits would increase work engagement level.…”
Section: Discussioncontrasting
confidence: 93%
“…This result is also consistent with a previous study 12) . In that study, educators, managers and police officers showed high levels of engagement, which was in contrast with a study conducted in China 10) in which support staff were more engaged compared with professional staff. At this moment, we do not have interventional evidence suggesting that educational methods or lifestyle habits would increase work engagement level.…”
Section: Discussioncontrasting
confidence: 93%
“…Nesse sentido, pode-se afirmar que os escores de engajamento no trabalho obtidos por meio da escala são invariantes para gênero e setor de trabalho e que esses grupos podem ser comparados entre si (Sass, 2011). Tais evidências dão, assim, sustentação aos estudos que vêm evidenciando a não existência de diferenças significativas entre os gêneros (Fong & Ng, 2012;Vasquez et al, 2015, Schaufeli, 2012 e entre trabalhadores do setor público e privado (Vigoda-Gadot, Eldor, & Schohat, 2012) no que diz respeito ao engajamento no trabalho. No presente estudo, essas diferenças foram testadas de forma mais rigorosa.…”
Section: Discussionunclassified
“…Estudos posteriores, conduzidos em amostras de diferentes países, com trabalhadores pertencentes a diversos grupos ocupacionais, confirmaram que a escala apresentava propriedades psicométricas adequadas (Fong & Ng, 2012;Nerstad, Richardsen, & Martinussen, 2010;Vazquez, Magnan, Pacico, Hutz, & Schaufeli, 2015).…”
unclassified
“…199 Cogin and Fish 283 found that the experience of sexual harassment was negatively linked with engagement in a cross-sectional study.…”
Section: Individual Perceptions Of Organisational and Team Factorsmentioning
confidence: 99%